Nanofabrication Principles and Applications - Papadopoulos, Christo (SpringerBriefs in Materials,, 2016)
This book provides an overview of the techniques and tools of nanostructure fabrication from state-of-the-art lithography to emerging self-assembly approaches. Top-down and bottom-up methodologies along with hybrid approaches are used to illustrate the fabrication of structures including integrated circuits, semiconductor quantum dots, metallic nanoparticles, carbon nanotubes, molecular structures, nanocomposites, arrays and superstructures. Nanofabrication applications in nanoelectronics, biotechnology, nanomechanical devices and nanophotonics will be examined. This brief will present the core concepts of nanofabrication relevant to researchers and industry in this important and rapidly evolving area.